(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
Expansion of functional possibilities of the use of combined designs in the construction, improvement of architectural expressiveness of buildings and structures determine the need for improved requirements to ensure the quality and reliability of means and methods of corrosion protection. Currently, the development of computational methods to assess the reliability and structural safety associated with the construction of in-formation-analytical database key parameters of corrosion condition of metal construction. Methodology. This way creates the basis for setting and implementing management tasks operational life of buildings and structures in corrosive environments by improving the quality and reliability of primary and secondary protection of steel structures based on the level of corrosion hazard. Results. When using the principles of the process approach is the formulation and implementation of tasks of management of operational service life in corrosive environments. The principles of ensuring safety in terms of corrosion risk include the rationale for the sequence of steps to evaluate the survivability of building structures based on the principles of robust design, improvement and control measures the primary and secondary corrosion protection. Scientific novelty. The implementation of protection measures against corrosion according to the corrosion risk criterion helps to ensure the requirements of reliability of building structures in accordance with the design provisions of limit state method and to solve the problems of control of technological security for the rated life of construction projects. objects. Practical significance. The proposed generalized indicators of the actual structures’ corrosion state determine the structure’s operability as a whole. The functional dependencies between the operability of the main and auxiliary structures are established. The relationship between the values of corrosion resistance indicators and metal structures durability are determined. Actual technical condition control consists of checking that the values of these indicators are within acceptable limits. Taking into account the degree of operating environment aggressiveness is one of the determining factors in order to ensure the secondary protection effectiveness against corrosion. This procedure is the basis for the rational specifications appointment for anti-corrosion protection systems with subsequent display in the design and technological documentation.